Charactherization Analog Rice based of White Canna Strach Adding with Soy Flour (Glicine Max) and Glycerol Monostearate - Jariyah; Sri Winarti; Yushinta Aristina Sanjaya; Setyandari Ayu Larasati (Future Science)
This research was aimed to analize the characteristics of analog rice made from white canna starch fortified with soybean flour and Glycerol Monostearate (GMS). The experimental design used was a completely randomized design (CRD) with two factors. The first factor is the proportion of white canna starch and soybean flour, the second factor is the concentration of the addition of GMS. The results of the analysis of raw materials showed that the water content of canna starch was 8.46%; ash content of 1.54%; starch content of 70.43%; amylose by 20.22% and amylopectin by 50.21%. The results of the analysis of the moisture content of soybean flour are 10.85%; ash content of 2.04%; and 39.18% protein content. The results of analog rice analysis showed that there was a significant interaction in the analysis of ash content, kamba density and protein content. The interaction results were not significant from the analysis of water content, rehydration power, expansion volume, starch content, amylose content and amylopectin content although each treatment showed significant differences. Sensory analysis was performed on analog rice. The results of sensory analysis of the aroma, taste, color and texture of analog rice obtained the best results at the proportion of 24% soy flour with the addition of 2% GMS. The results showed a moisture content of 7.18%, ash content of 1.9%5, protein content of 14.05%, starch content of 65.79%, amylose 18.81%, amylopectin 46.97%, rehydration power 67 (g/ml), kamba density 55.3 (g/ml). ml), and the expansion volume was 116.67 g/ml.